Sleepy Melodies: Android-Based Application For Hypno Sleeping Process In Babies 0-6 Months - Pratiwi, Meilicha Anggraini; Vista, Nabila; Wati, Wahida Rahma; Wahyuni, Sari (Poltekkes Kemenkes Palembang, 2023)
The postpartum period is the period of six weeks after delivery or 42 days from the birth of the baby until the reproductive organs return to their normal pre-pregnancy state. During the postpartum period, only some postpartum mothers managed to adjust to the post-natal psychological change phase, while others did not manage to adjust and experienced psychological disorders. According to Nasri (2017), one of the problems of postpartum mothers is psychological problems, the most common affective or mood disorders found in postpartum women are postpartum blues. According to Ibrahim (2012) many factors are suspected to be the trigger for the postpartum blues including hormonal factors, age, parity, experience in the process of pregnancy and childbirth, education, marital status, unwanted pregnancies, history of mental disorders, socioeconomic, and social support. . In addition, readiness in caring for babies is also a factor in the occurrence of post partum blues if the baby is fussy for a long time. One way for mothers who are affected by the postpartum blues due to difficulties in caring for babies, especially putting babies to sleep, is to use the hypno sleeping method with white noise media. According to the National Sleep Foundation, white noise can give babies a better sense of sleep, without being distracted by distracting high-pitched sounds.Along with the industrial revolution 4.0 which changed the way humans work from manual use to digitalization, the representation of applications that can be used in community service. The aim of this study was to produce an application Sleppy Melodies Android-based to help mothers make it easier for their children to sleep. This research design uses the model Research and Development. Sources of data for this study came from mothers with children aged 0-6 months, midwives, material experts, and media experts. There were 87% of mothers and 89% of midwives who responded very well to the application Sleepy Melodies Android-based. In this study it can be concluded that application Sleepy Melodies android-based declared eligible by 86% to be used by health workers and mothers in improving the quality of infant sleep.